2021
DOI: 10.1016/j.tranpol.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, community response, public policy, and travel patterns: A tale of Hong Kong

Abstract: The COVID-19 outbreak has necessitated a critical review of urban transportation and its role in society against the backdrop of an exogenous shock. This article extends the transportation literature regarding community responses to the COVID-19 pandemic and what lessons can be obtained from the case of Hong Kong in 2020. Individual behavior and collective responsibility are considered crucial to ensure both personal and community wellbeing in a pandemic context. Trends in government policies, the number of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…Second, real-time NPIs in the past few months are recorded and simulated in our model to understand their effectiveness. However, preventive behaviors on the individual level (e.g., human mobility and face covering), which dictate the likelihood of infection, are not considered in our simulation [ 43 , 44 ]. Thus, future extensions of the model should emphasize these behavioral factors to better estimate virus transmissibility.…”
Section: Discussionmentioning
confidence: 99%
“…Second, real-time NPIs in the past few months are recorded and simulated in our model to understand their effectiveness. However, preventive behaviors on the individual level (e.g., human mobility and face covering), which dictate the likelihood of infection, are not considered in our simulation [ 43 , 44 ]. Thus, future extensions of the model should emphasize these behavioral factors to better estimate virus transmissibility.…”
Section: Discussionmentioning
confidence: 99%
“…How the required reduction of mobility impacts the economic activity is not clear, as some researchers argue that increasing activity in parks and groceries/pharmacies has much less effect on the reproductive rate than staying at home [ 44 ]. Travel patterns appear to have a huge impact in the propagation of the virus, requiring a combination of sensible public policies and the willing collaboration of the community, as demonstrated by the case of Hong Kong [ 45 ]. Big data extensive studies have found that imposed public policies play a small role in the reduction of mobility [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, real-time NPIs in the past few months are recorded and simulated in our model to understand their effectiveness. However, preventive behaviors on the individual level (e.g., human mobility, face covering), which dictate the likelihood of infection (Chan et al, 2021;Cowling et al, 2020), are not considered in our simulation. Thus, future extensions of the model should emphasize these behavioral factors to better estimate virus transmissibility.…”
Section: Discussionmentioning
confidence: 99%